SLEEP HYGIENE AS AN IMPORTANT COMPONENT OF PREVENTING HEALTH DISORDERS IN STUDENTS - Yuldasheva F. U.; Buranboev Kh. S.; Kamalov R. K.; Orifzhonova N. R. (Web of Journals Publishing, 2024)
The article analyzes the role of sleep hygiene in preventing health disorders in students. The main aspects of sleep hygiene are considered, including the regularity of the regime, duration and quality of sleep, as well as their impact on physical and psycho-emotional well-being. Particular attention is paid to specific factors affecting students, such as academic workload, stress and the use of electronic devices.
Keywords: Sleep hygiene, circadian rhythms, students, prevention, sleep disorders, healthy lifestyle, sleep and performance, psycho-emotional state, chronic sleep deprivation, daily routine, sleep quality, environmental factors.